2010
DOI: 10.1002/bit.22732
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the productivity of catalytic biofilms on solid supports in membrane aerated reactors

Abstract: A new solid support membrane aerated biofilm reactor was designed for the synthesis of enantiopure (S)-styrene oxide utilizing Pseudomonas sp. strain VLB120DeltaC growing in a biofilm as biocatalyst. In analogy to traditional packed bed systems, maximizing the volumetric oxygen mass transfer capability (k(L)a) was identified as the most critical issue enabling a consistent productivity, as this parameter was shown to directly influence biofilm growth and biotransformation performance. A microporous ceramic uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 66 publications
0
37
0
3
Order By: Relevance
“…strain VLB120⌬C made it possible to directly monitor live cells in the biofilm. Biofilms were cultivated in a custommade flow-cell system, which allowed the real-time fluorescence-based optical analysis of cell physiology and the direct addition of the solvent styrene to the biofilm based on a diffusion-controlled substrate delivery mechanism using a permeable silicone membrane (12). A schematic view of the setup is shown in the figure in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…strain VLB120⌬C made it possible to directly monitor live cells in the biofilm. Biofilms were cultivated in a custommade flow-cell system, which allowed the real-time fluorescence-based optical analysis of cell physiology and the direct addition of the solvent styrene to the biofilm based on a diffusion-controlled substrate delivery mechanism using a permeable silicone membrane (12). A schematic view of the setup is shown in the figure in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…than their planktonic or freely swimming counterparts (7,9,16,19,29,40). There has been growing interest in recent years in the exploitation of these robust catalysts for biotechnological applications (e.g., biotransformations) to produce value-added chemicals (10,11,12,27). These studies have shown that the use of biofilms may overcome major bottlenecks in classical biocatalysis processes, such as substrate/product toxicity and short-term biocatalytic stability.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, controlling biofilm-based bioprocesses is very challenging because of the intrinsic heterogeneous and dynamic properties of biofilms (10,11). Previous studies have shown that either unfavorable environmental conditions (e.g., exposure to toxic contaminants) or variations in nutrient supply (e.g., dissolved O 2 availability) could cause cell dispersal from biofilms (12)(13)(14)(15), resulting in a decrease in the performance of the biofilm-based bioprocesses.…”
mentioning
confidence: 99%